Anticancer effect of the traditional Chinese medicine herb Maytenus compound via the EGFR/PI3K/AKT/GSK3β pathway - Zeng, Baozhen; Ge, Chunlei; Zhao, Wentao; Fu, Kaicong; Liu, Lin; Lin, Zhuying; Fu, Qiaofen; Li, Zhen; Li, Ruilei; Guo, Huan; Li, Chunyan; Zhao, Liufang; et al. (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Cancer is a leading cause of death worldwide; folk anticancer medicinal plants have applied for cancer treatment. The Maytenus compound tablet as traditional Chinese compound medicine has been approved for alleviating hyperplasia of mammary glands, whether it can inhibit cancer still unknown. The study was to evaluate the anticancer activity of the Maytenus compound tablet. Methods: MTS assay evaluated the anti-proliferation effect of the Maytenus compound on H226, A2058, 786O and HeLa cancer cells and two normal epithelial cell lines, namely, 16HBE and Hecate. Nude mouse xenograft tumor model using H226 and HeLa cells examined the drug’s anticancer effect in vivo. Western blot assay studied the possible mechanism. Results: The Maytenus compound indicated obvious ability to against proliferation in four strains of cancer cells, particularly against H226 cells by an IC50 of 85.47±10.06 µg/mL and against HeLa cells by an IC50 of 128.74±17.46 µg/mL. However, it had a low cytotoxicity in human normal epithelial cell lines 16HBE with an IC50 of 4,555.86±25.21 µg/mL and Hecate with an IC50 of 833.56±181.88 µg/mL. The Maytenus compound at the 2.45 g/kg oral dosages inhibited the proliferation of H226 cells and HeLa cells in nude mouse with inhibitory rates of 36.06% and 26.45%, respectively, and no organ toxicity. The Maytenus compound could significantly downregulate the expression of pEGFR, pPI3K, pAKT, pGSK3β, β-catenin, and c-MYC and upregulate the protein expression of GSK3β. Conclusions: The Maytenus compound has significant anticancer activities against human cancer H226 and HeLa cells both in vitro and in vivo, highlighting it may be an anticancer medicine.